PSX-38 Reproductive performance of Dorper ewes with varying days post-partum to ram introduction in the non-breeding season - Flores, Victor V (J Anim Sci, 2019)
With the decrease of a wool favored market, hair type sheep have become increasingly popular for lamb markets. In Texas, the most popular hair type breed of sheep is the Dorper. Various breed characteristics make the Dorper sheep an excellent candidate for an accelerated lambing system. Reproductive performance of Dorper ewes with various lengths of post-partum interval, during the traditional non-breeding season, was determined. During May (13L:11D), 2+ yr-old multiparous ewes (n = 28) were joined with a fertile ram for 30 d. Weekly blood samples were taken for progesterone analysis. Ewes were blocked according to length of post-partum interval (lamb to ram): short (SPP; n = 10, 100 ± 2.7 d), mid (MPP; n = 11, 130 ± 0.68 d) and long (LPP; n = 7, >200 d). Weaning age of lamb(s) from previous parturition was similar for SPP (62 ± 3.2 d) and MPP (67 ± 0.6 d). Interestingly, 11% of the ewes had a functional CL at initiation of the study (P(4) > 1.5 ng/mL). Mean body condition score for SPP, MPP, and LPP ewes were 2.8 ± 0.08, 3.1 ± 0.09, and 3.7 ± 0.08, respectively. Pregnancy rates were similar between MPP (100%), LPP (100%) and SPP (60%). Overall, pregnancy rate was 87% and a lamb crop (lambs per ewe exposed) was 1.3 ± 0.09. Twinning rate for SPP, MPP, and LPP was 20%, 73%, and 43%, respectively. Pregnancy rate in SPP ewes may indicate carryover of the suppressive effects of lactation and suckling. Results suggest a lamb to ram interval of >100 d is sufficient for response to the ram effect and resumption of estrous cycles in a majority of ewes during photoperiod of 13L:11D. We conclude Dorper sheep have the reproductive capacity to successfully meet the production goals of accelerated lambing systems and thus, the potential for optimized lamb production.